The Role of Training and Development: Models & Performance in Iranian Organisations - Asl, Samad jabbari (Gyan Management Journal, 2009)
Training and development is a systematic process far analyzing and improving employee performance in organizations. it encompasses all of the performance analysis, training, career development, and organization development activities provided by organizations to hel/1 both employees and organi{fttions achieve their goals. The main purpose of this study is to identify selected successful models of training and development as they may be appluable to Iranian organi{.ations, and describe selected methods of needs assessment for training and dwelopment programs far employers and employees. The study suggest kind of ways far developing a comprehensive pum far the creation of effective employee training and development program in Iran, and also study conducted by engagi11g in comprehensive review and critique of the existing literature on training and
Keywords: ISD; HPD; PBID; TQM